Influence of Preservation of Normal Knee Contact Stress on Other Compartments with respect to the Tibial Insert Design for Unicompartmental Knee Arthroplasty. (14th November 2019) - Koh, Yong-Gon; Park, Kyoung-Mi; Kang, Kyoung-Tak
Abstract : Recent advances in imaging technology and additive manufacturing have led to the introduction of customized unicompartmental knee arthroplasty (UKA) that can potentially improve functional performance due to customized geometries, including customized sagittal and coronal curvature and enhanced bone preservation. The purpose of this study involved evaluating the biomechanical effect of the tibial insert design on the customized medial UKA using computer simulations. We developed sagittal and coronal curvatures in a native knee mimetic femoral component design. We utilized three types of tibial insert design: flat, anatomy mimetic, and conforming design. We evaluated contact stress on the tibial insert and other compartments, including the lateral meniscus and articular cartilage, under gait and squat loading conditions. For the conforming UKA design, the tibial insert and lateral meniscus exhibited the lowest contact stress under stance phase gait cycle. However, for the conforming UKA design, the tibial insert and lateral meniscus exhibited the highest contact stress under swing phase gait cycle. For the flat UKA design, the articular cartilage exhibited the lowest contact stress under gait and squat loading conditions. The anatomy mimetic UKA design exhibited the most normal-like contact stress on the other compartments under gait and squat loading conditions. The results reveal the importance of conformity between the femoral component and the tibial insert in the customized UKA. Based on the results on the femoral component as well as the tibial insert in the customized UKA, the anatomy mimetic design preserves normal knee joint biomechanics and thus may prevent progressive osteoarthritis of the other knee compartments.